Disseminated Prostate Cancer Cells Can Instruct Hematopoietic Stem and Progenitor Cells to Regulate Bone Phenotype - Joseph, Jeena (2012)
Prostate cancer (PCa) metastases and hematopoietic stem cells (HSCs) frequently home to the bone marrow where they compete to occupy the same HSC niche. We have also shown that under conditions of hematopoietic stress, HSCs secrete the bone morphogenetic proteins (BMPs)-2 and BMP-6 that drives osteoblastic differentiation from mesenchymal precursors. Because it is not known, we examined if metastatic PCa cells can alter regulation of normal bone formation by HSCs and hematopoietic progenitor cells (HPCs). HSC/HPCs isolated from mice bearing non-metastatic and metastatic tumor cells were isolated and their ability to influence osteoblastic and osteoclastic differentiation was evaluated. When the animals were inoculated with the LNCaP C4-2B cell line which produces mixed osteoblastic and osteolytic lesions in bone, HPCs but not HSCs were able to induced stromal cells to differentiate down an osteoblastic phenotype. Part of the mechanism responsible for this activity was the production of BMP-2. On the other hand, when the animals were implanted with PC3 cells that exhibits predominantly osteolytic lesions in bone, HSCs derived from these animals were capable of directly differentiating into tartrate-resistant acid phosphatase (TRAP) positive osteoclasts through an interleukin-6 (IL-6) mediated pathway. These studies for the first time identify HSC/HPCs as novel targets for future therapy involved in the bone abnormalities of PCa.